Insect Migration Flux Estimation Based on Statistical Hypothesis for Entomological Radar - Teng Yu; Muyang Li; Weidong Li; Jiong Cai; Rui Wang; Cheng Hu (Remote Sensing, 2022)
Measuring migration flux with entomological radar is of great importance to assess the biomass of migratory insects and study the influence of insects on the ecosystem. However, the migration flux is measured with a large quantity of errors for the entomological radar without the ability of in-beam angle measurement, because the insect RCS is measured with the assumption that the insect flies over the beam center. When the insect does not pass through the beam center, the measured RCS is less than the true value. To improve the estimation accuracy of migration flux, a new estimation method of migration flux based on statistical hypothesis is proposed for radars working in the fixed-beam vertical-looking mode. This method avoids the RCS measurement error caused by the offset of the insect trajectory to the radar beam center by assuming that the insect flight trajectory is evenly distributed in the beam and calculating the average value of flux. This method is extended to be used in fixed-beam arbitrary pointing mode and a new proposed scanning mode. The effectiveness of the proposed method is verified by simulations and migration insect data measured by a radar.